Testing of interposer-based 2.5D integrated circuits - Wang, Ran; Chakrabarty, Krishnendu (Springer, 2017)
This book provides readers with an insightful guide to the design, testing and optimization of 2.5D integrated circuits. The authors describe a set of design-for-test methods to address various challenges posed by the new generation of 2.5D ICs, including pre-bond testing of the silicon interposer, at-speed interconnect testing, built-in self-test architecture, extest scheduling, and a programmable method for low-power scan shift in SoC dies. This book covers many testing techniques that have already been used in mainstream semiconductor companies. Readers will benefit from an in-depth look at test-technology solutions that are needed to make 2.5D ICs a reality and commercially viable. Provides a single-source guide to the practical challenges in testing of 2.5D ICs; Presents an efficient method to locate defects in a passive interposer before stacking; Describes an efficient interconnect-test solution to target through-silicon vias (TSVs), the redistribution layer, and micro-bumps for shorts, opens, and delay faults; Provides a built-in self-test (BIST) architecture that can be enabled by the standard TAP controller in the IEEE 1149.1 standard; Discusses two ExTest scheduling strategies to implement interconnect testing between tiles inside an SoC die; Includes a programmable method for shift-clock stagger assignment to reduce power supply noise during SoC die testing in 2.5D ICs.
Keywords: Integrated circuits.; elektronické knihy; electronic books